Hubungan Dukungan Keluarga dengan Kepatuhan Diet Pasien Diabetes Mellitus Tipe 2 di Poli Klinik Penyakit Dalam RSI Siti Khadijah Palembang - Lela Aini; Lenny Astuti; Fitri Anita (Malahayati Nursing Journal, 2024)
ABSTRACT One of the disease that has a significant increasing in the number of sufferers is Diabetes Mellitus (DM). Diabetes that is widely experienced in Indonesia, namely type 2 DM covers more than 90% of the entire diabetic population. Type 2 DM occurs due to defects in insulin secretion or insulin resistance and DM conditions develop when insulin secretion is inadequate (Bahagia et al., 2018). The aim of this study is to know the relationship between family support and dietary compliance in patients with type 2 diabetes mellitus at the Internal Medicine Polyclinic, RSI Siti Khadijah Palembang. Using a non-experimental design with a correlation study (Correlation Study). The population of this study were all type 2 DM sufferers who were treated at Siti Khadijah Palembang Islamic Hospital from October to December 2022 with a total of 60 patients. Sampling in this study was carried out by purposive sampling with a total sample of 42 respondents. Data analysis uses univariate and bivariate. This study obtained a p-value of 0.033 so that a p-value 0.05, which means that H1 is accepted, that is, there is a relationship between family support and dietary compliance of diabetes mellitus patients at the Internal Medicine Polyclinic RSI Siti Khadijah Palembang. Suggestions for future researchers to be able to discuss the relationship between family support and compliance with the DM diet, especially in instrumental support. Keywords: Diabetes Mellitus Type 2, Family Support, Diet Compliance  ABSTRAK Diabetes Melitus (DM) merupakan penyakit yang banyak diderita oleh Masyarakat di Indonesia. Jenis diabetes yang umum terjadi adalah diabetes tipe 2 (90% dari populasi penderita DM). DM tipe 2 terjadi akibat kerusakan sekresi insulin serta resistensi insulin in adekuat (Bahagia et al., 2018). Tujuan dalam penelitian ini Diketahinya Hubungan Dukungan Keluarga Dengan Kepatuhan Diet Pasien Diabetes Mellitus Tipe 2 di Poli Klinik Penyakit Dalam RSI Siti Khadijah Palembang. Menggunakan desain non eksperimen dengan studi korelasi (Correlation Study). Populasi penelitian ini adalah seluruh penderita DM tipe 2 yang dirawat di RS Islam Siti Khadijah Palembang dari bulan Oktober – Desember Tahun 2022 sebanyak 60 pasien, dengan jumlah sampel sebanyak 42 responden yang dipilih dengan teknik purposive sampling. Hasil analisis diperoleh p value sebesar 0,033 0,05. Dapat disimpulkan bahwa ada hubungan antara dukungan keluarga dengan kepatuhan diet pasien diabetes mellitus di Poliklinik Penyakit Dalam RSI Siti Khadijah Palembang. Saran bagi peneliti selanjutnya agar dapat mengidentifikasi hubungan dukungan keluarga dengan kepatuhan menjalankan diet DM khususnya pada dukungan instrumental. Kata Kunci: Diabetes Mellitus Tipe 2, Dukungan Keluarga, Kepatuhan Diet